METHODICAL TOOLS FOR DEVELOPMEN OF STRATEGIC ALTERNATIVES IN FORMING COMPETITIVE STRATEGY OF THE MINING AND CHEMICAL COMPANY - Angelica L. Gendon; Alina A. Ilinova (Статистика и экономика, 2016)
Paper is devoted to development and usage of methodical tools of formation of strategic alternatives of competitive strategy of the mining and chemical company. Approaches to development of competitive advantages of the domestic mining and chemical companies in the conditions of a maturity industry are defined. The tools of formation of strategic alternatives which cornerstone different types of the competitive advantages actual for the industry are developed.